2018
DOI: 10.1007/s40263-018-0559-8
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic-Associated Symptoms of Tourette Syndrome: A Systematic Review

Abstract: Tics can be a disturbing adverse effect of antipsychotics. Clinicians need to be particularly vigilant when initiating and modifying antipsychotic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The main finding of this case report is the re-emergence of vocal and motor tics in a patient with a history of TS, soon after initiation of chlorpromazine therapy. Although it may seem paradoxical as antipsychotics are the first-line treatment for TS, several cases of antipsychotic-induced tics have been previously reported [ 5 - 10 ]. One systematic review by Kim et al identified 60 cases of antipsychotic-induced tics, with 30 cases associated with first-generation antipsychotics and 27 with second-generation antipsychotics [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main finding of this case report is the re-emergence of vocal and motor tics in a patient with a history of TS, soon after initiation of chlorpromazine therapy. Although it may seem paradoxical as antipsychotics are the first-line treatment for TS, several cases of antipsychotic-induced tics have been previously reported [ 5 - 10 ]. One systematic review by Kim et al identified 60 cases of antipsychotic-induced tics, with 30 cases associated with first-generation antipsychotics and 27 with second-generation antipsychotics [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it may seem paradoxical as antipsychotics are the first-line treatment for TS, several cases of antipsychotic-induced tics have been previously reported [ 5 - 10 ]. One systematic review by Kim et al identified 60 cases of antipsychotic-induced tics, with 30 cases associated with first-generation antipsychotics and 27 with second-generation antipsychotics [ 5 ]. In addition, the occurrence of vocal tics was significantly higher in the first-generation antipsychotic use as compared to second-generation antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many limitations come from the fact that most of our included studies are case reports/series. These include the risk of publication bias and that our included cases may not represent a random sample of patients treated with clozapine [82]. However, we used a systematic approach to including and analyzing the cases and this may have reduced some bias.…”
Section: Managementmentioning
confidence: 99%